Affective touch awareness in mental health and disease relates to autistic traits – An explorative neurophysiological investigation. (30th November 2016) - Croy, Ilona; Geide, Helen; Paulus, Martin; Weidner, Kerstin; Olausson, Håkan
Abstract: Affective touch is important for social interaction within families and groups and there is evidence that unmyelinated C tactile fibers are involved in this process. Individuals with autism spectrum disorders show alterations in the perception and processing of affective touch. sThus, we hypothesized that affective touch awareness based on C tactile fiber activation is impaired in individuals with high levels of autistic trait. The pleasantness perception of optimal and suboptimal C tactile stimuli was tested in an explorative study in 70 patients recruited from an outpatient psychotherapy clinic and 69 healthy comparison subjects. All participants completed questionnaires about autistic traits, depressive symptomatology, childhood maltreatment, and about the daily amount of touch. Relative to comparison subjects, patients reported engaging in touch less frequently in daily life and rated touch less pleasant. Reduced valence ratings of touch were explained by childhood maltreatment but not by any particular disorder or depression severity. Among all tested variables, the affective touch awareness correlated with autistic traits only - in patients as well as in comparison subjects. Taken together, individuals with mental health issues have a lower baseline of expression and reception of affective touch. Autistic traits and childhood maltreatment modulate the experience of affective touch. Highlights: Patients reported engaging in touch less than controls. Patients rate touch in general less pleasant than controls. Reduced valence relate to childhood maltreatment but not to depression severity. Appreciation of C tactile stimuli correlates with autistic traits.